Preservice teachers studying video narratives of student argumentation - Van Ness, Cheryl K.; Maher, Carolyn A. (Universitas Papua, 2023)
National Standards in the teaching of mathematics call for teachers to pay attention to the nature of student problem solving and argumentation in learning mathematics. In order to attend to student argumentation, resources are needed in which student argumentation can be observed. This paper reports the result of a preservice-teacher intervention study in which teachers described student argumentation in a video narrative before and after instruction, which included video narratives designed to highlight argumentation. Pre- and post-assessment of teachers’ identification of student argumentation used a mixed-methods analysis to investigate growth in noticing more of children’s argumentation across a video narrative that was created with 15 video clips that displayed student argumentation in the classroom. Results showed that growth occurred in cycles that described shorter argumentation stories within the longer narrative. On average, over 85% of the teachers consistently exhibited growth at the end of a cycle of 3 to 6 video clips that provided a complete story of several children’s argumentation, in contrast to growth on specific clips that showed a particular child’s argument. Results suggest the enhanced value of using video episodes that reveal complete stories of student argumentation in a classroom for teacher intervention.